A Civil War Gunboat in Pacific Waters : Life Aboard the USS Saginaw - Van Tilburg, Hans (Book collections on Project MUSE., 2010)
In 1870, the ship sank at one of the world's most remote coral reefs; her crew was rescued sixty-eight days later after a dramatic open-boat voyage. More than 130 years later, Hans Van Tilburg led the team that discovered and recorded the Saginaw' s remains near the Kure Atoll reef.